BELARUS: TRANSFORMATION FROM AUTHORITARIANISM TOWARDS SULTANISM - Rouda, Uladzimir (Baltic Journal of Political Science, 2012)
The article consists of three parts. Firstly, the author considers the main concepts of the political regime in Belarus. Such an analysis includes the concepts of hybrid, authoritarian, and neo-patrimonial regimes. The second part deals with the reasons for Belarusian retreat from democratic standards, namely the Russian factor in Belarusian politics. President Vladimir Putin and Russian bureaucracy are afraid to lose Belarus in case Aliaksandr Lukashenka is removed from absolute power. The authoritarian regime in Russia has sponsored autocracies in the post-Soviet space, ensuring their dependence on Moscow. In the third part, the author analyses the transformation of the Belarusian regime, using the variables of the role of leadership, the state of pluralism, the role of ideology, the character of political mobilization, and the state of human rights. During a very short period of Lukashenka’s rule, we have witnessed a constant tightening of dictatorship rule, which has led the Belarusian regime to the point of a hybrid authoritarian-sultanistic regime (2006) and almost classical sultanism (2010). Such regimes as Belarusian can only be changed through the mobilization of public protest from below. Besides, the Belarusian semi-sultanism is not sustainable.